1992
DOI: 10.1103/physrevlett.69.3751
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution transmission electron microscopy of pressure-amorphized α-quartz

Abstract: a-quartz becomes x-ray amorphous when compressed, at ambient temperature, by pressures of 25 to 30 GPa [Hemley et al.. Nature 334, 5 (1988)1. The relationship between pressure-amorphized and melt-quenched silica is of great interest. The most fundamental characteristic of melt-quenched silica is its lack of periodicity at the atomic level. We report here that high-resolution electron microscopy shows that a-quartz, pressure amorphized at 30.5 GPa is, as is conventional melt-quenched silica, amorphous at the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…2(e)] shows that the topology is similar to that found in densified glass quenched from high pressure [38]. We conclude that the densified glass obtained in our simulations is a good model for the material recovered in experiments [2,3,5].…”
supporting
confidence: 71%
See 1 more Smart Citation
“…2(e)] shows that the topology is similar to that found in densified glass quenched from high pressure [38]. We conclude that the densified glass obtained in our simulations is a good model for the material recovered in experiments [2,3,5].…”
supporting
confidence: 71%
“…Quartz was reported to collapse into a poorly crystallized metastable structure named quartz II at around 21 GPa [1], i.e., well into the region of stability of stishovite, followed either by amorphization [2][3][4][5][6][7] or by transition to metastable high-density crystalline polymorphs, e.g., P 2 1 /c structure [8][9][10]. The pressure-induced amorphization (PIA) of quartz has been examined either from a thermodynamical point of view (as a density-driven transition to the reentrant highly viscous liquid [2,11], a phenomenology first observed in ice [12]), and from a mechanical standpoint (as an elastic/dynamic instability of the quartz lattice [13][14][15][16][17][18][19][20]), as well as from a crystallographic perspective, as the result of ordering and displacive mechanisms from a common parent structure [21].…”
mentioning
confidence: 99%
“…The unusual high-pressure behavior of the Si02 polymorph a-quartz and its structural analogs has been the subject of recent experimental [1][2][3][4][5][6][7][8][9][10][11][12] and theoretical [13][14][15][16][17][18][19][20] investigations. Potentially anomalous properties of the material recovered from high pressure have been of particular interest [1][2][3]18,20].…”
mentioning
confidence: 99%
“…It is now established that when pressurized well outside of its stability field at 300 K, a-quartz gradually transforms to an amorphous state [1,[3][4][5]7,8]. Despite the growing number of investigations, no detailed in situ structural studies near the onset of amorphization have been reported.…”
mentioning
confidence: 99%
“…The amorphous nature of samples of pressurized SiC>2 was originally ascertained using x-ray techniques [23]. Initial transmission electron microscopy (TEM) measurements [24] up to 30 GPa showed no evidence of crystallinity and no difference from ordinary "fused" silica. More recent TEM experiments [25,26] show some evidence of remnant crystallinity if the maximum pressure is below 30 GPa.…”
mentioning
confidence: 99%